Patient Satisfaction with Home Exercise Programs in Physical Therapy - ALHADDAD, OMAR MOHAMMED; Bukhari, Abdulaziz Abdullah; Shiqdar, Anas Mohammed; Alqurashi, Mazen Salman; Jan, Ibrahim Akram; Alharbi, Majid Dakhil; Alesmail, Ali Saleh; Alkhaibary, Mansour Abdullah Hussein; Alhassawi, Ahmed Tariq; Albariqi, Ahmed Ali Abu Bakr; et al. (Journal of Posthumanism, 2024)
Home exercise programs are vital in maintaining physical therapy outcomes but depend on patient satisfaction, adherence, and effectiveness. Patient satisfaction was explored in a study of satisfaction with home exercise programs among 120 patients at three physical therapy centers in Atlanta, Georgia. One hundred twenty patients were given a cross-sectional survey on comprehension of exercise instruction, frequency of adherence, and barriers to adherence. Fifty patients reported high satisfaction and specifically cited clear, illustrated instructions as a primary factor, 45 reported being neutral, and 25 reported dissatisfaction. The primary barriers cited were obscure instructions by 55 patients and time demands by 50. These results show that explicit instructional materials are important in satisfaction, while logistical barriers prevent adherence. The study proposes incorporating digital support in video tutorials and regular clinician reviews to increase patient satisfaction and adherence and improve rehabilitation outcomes.